2011
DOI: 10.1080/20445911.2011.594433
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of emotion–cognition interactions: A review of evidence from brain imaging investigations

Abstract: Complex dynamic behaviour involves reciprocal influences between emotion and cognition. On the one hand, emotion is a “double-edged sword” that may affect various aspects of our cognition and behaviour, by enhancing or hindering them and exerting both transient and long-term influences. On the other hand, emotion processing is also susceptible to cognitive influences, typically exerted in the form of emotion regulation. Noteworthy, both of these reciprocal influences are subjective to individual differences th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
255
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 303 publications
(283 citation statements)
references
References 181 publications
(312 reference statements)
18
255
0
10
Order By: Relevance
“…For example, within the field of visual attention researchers propose that top-down processing is characterized by goal-directed behavior whereas bottom-up processing refers to the automatic capture of attention by salient information in the environment regardless of task demand [9]. It has been argued that during tasks investigating the effects of emotion on cognition it is likely that both processing strategies are evident [7]. For instance during cognitive tasks involving emotional distractors, it is suggested that the influence of the emotional distraction depends on interactions between neural systems that allow an individual to stay focused on the task as well as systems responsible for the processing of emotional information [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, within the field of visual attention researchers propose that top-down processing is characterized by goal-directed behavior whereas bottom-up processing refers to the automatic capture of attention by salient information in the environment regardless of task demand [9]. It has been argued that during tasks investigating the effects of emotion on cognition it is likely that both processing strategies are evident [7]. For instance during cognitive tasks involving emotional distractors, it is suggested that the influence of the emotional distraction depends on interactions between neural systems that allow an individual to stay focused on the task as well as systems responsible for the processing of emotional information [7].…”
Section: Introductionmentioning
confidence: 99%
“…At the behavioral level emotion has been shown to influence multiple aspects of cognition including working memory [1], task shielding [2], attentional control [3], and visual attention [4,5,6]. At the neural level research has shown that the prefrontal cortex (PFC) is involved in emotional processing during cognitive task completion; see [7,8] for recent compressive reviews of this research area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the hippocampus and the associated parahippocampal areas have been extensively studied in memory research [2][3][4][5] . Also, the role of the amygdala has been frequently emphasized in research examining emotion processing and emotion-cognition interactions [6][7][8][9][10][11] . Recently, various MTL regions have also received attention in the emerging field of personality neuroscience, which links the structure and function of these and other brain regions to individual variation in personality traits 12 .…”
Section: Introductionmentioning
confidence: 99%